Biomechanical analysis of cervical spine sagittal stiffness characteristics - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The orientation of the loading, along which the minimum and maximum displacements occur, can be described as the principal axis. This work presents a model to determine extremums of the compliance of the cervical spine and corresponding principal axis, given the pose and flexibility of each functional cervical unit. As the cervical model Of C-2-C-7 section is flexed, it becomes tensionally stiffer and as the structure is extended, it becomes compressively stiffer. The opposite is true for the model including the atlanto-occipito-axial complex suggesting a compressively stiffer column as it is flexed and a tensionally stiffer structure as it is extended. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: cervical spine; posture; principal displacement; compliance; BEAM-COLUMN; MODEL; EXTENSION; STRENGTH; FAILURE; FLEXION; TRAUMA